A novel temperature-stable Ba2-xCaxMgTi5O13 microwave dielectric ceramic. Issue 2 (February 2020) - Dai, Qianlong; Zuo, Ruzhong; Xu, Yudong; He, Liangguo
Abstract: The Ba2-x Cax MgTi5 O13 (0 ≤ x ≤ 0.3) microwave dielectric ceramics were for the first time prepared via a conventional solid-state reaction method. A small amount of Ca 2+ can dissolve into the lattice by forming solid solutions with a monoclinic structure (C2/m) and further influence the sintering behavior, grain growth and microwave dielectric properties of Ba2-x Cax MgTi5 O13 ceramics. Both increase of εr and decrease of Qxf with x should be associated with increased lattice distortion and uneven grain growth although the sample density and the ratio of the ionic polarizability to the molar volume show little variation. Moreover, the A-site bond valence and τf indicate a close relation in current study, such that the Ca 2+ substitution can induce an increase of τf values. The optimum microwave dielectric properties of εr ∼ 29.3, Qxf ∼ 30, 870 GHz (6.5 GHz), and a near-zero τf ∼ +2.1 ppm/°C can be contained in the x = 0.15 ceramic sintered at 1160 °C.